2015
DOI: 10.1128/jvi.00274-15
|View full text |Cite
|
Sign up to set email alerts
|

ORF45-Mediated Prolonged c-Fos Accumulation Accelerates Viral Transcription during the Late Stage of Lytic Replication of Kaposi's Sarcoma-Associated Herpesvirus

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) naturally infects humans, and over 95% of healthy persons have no symptoms. KSHV causes three types of malignancies in immunosuppressed patients: Kaposi's sarcoma, body cavity-based lymphoma, and multicentric Castleman's disease (1-3). KSHV establishes a latent infection in most infected cells, whereas a small proportion of cells develop lytic infection. The genetic profiles of KSHV-infected populations differ from those of uninfected populations, with host cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…In addition to HCMV, other herpesviruses modulate AP-1 during infection. The Epstein Barr virus (EBV) protein, BGLF2, and the Kaposi’s sarcoma-associated herpesvirus (KSHV)-encoded ORF45 both activate the AP-1 signaling pathway to promote viral gene expression, replication, and survival (37, 38). EBV also encodes an AP-1 homolog, BZLF1, which, like AP-1, supports resting B cell proliferation and binds methylated EBV promoters critical for reactivation (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HCMV, other herpesviruses modulate AP-1 during infection. The Epstein Barr virus (EBV) protein, BGLF2, and the Kaposi’s sarcoma-associated herpesvirus (KSHV)-encoded ORF45 both activate the AP-1 signaling pathway to promote viral gene expression, replication, and survival (37, 38). EBV also encodes an AP-1 homolog, BZLF1, which, like AP-1, supports resting B cell proliferation and binds methylated EBV promoters critical for reactivation (39).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we revealed that ORF45 induces sustained ERK-RSK activation and plays an essential role in KSHV lytic replication, and an ORF45-null or F66A mutation in ORF45 abolishes its activation and significantly decreases lytic replication (12)(13)(14)(15). Similarly, the inhibition of RSK activation by inhibitors or short hairpin RNAs (shRNAs) blocks both latent and lytic cycles (12,16), indicating that RSK is an effective target for disrupting KSHV lytic replication and persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…4C, middle). Interestingly, although the expression of the latent gene LANA was not affected, the expression of the latent genes vCyclin and vFLIP was inhibited to the same extent as the lytic genes, probably because their expression was increased during lytic replication similar to the lytic genes (20,21) and ORF45-induced c-Fos activation upregulated their transcription (14); thus, the TAT-10F10 peptide inhibits ORF45-mediated activation of the ERK-RSK-c-Fos pathway and, consequently, viral transcription. In addition, vFLIP is translated through a viral internal ribosome entry site (IRES) (22) that is upregulated by eIF4B phosphorylation (13,23), and inhibition of eIF4B phosphorylation by TAT-10F10 decreases vFLIP translation.…”
Section: Development Of a Nontoxic Cell-permeable Orf45 Tat-10f10 Pepmentioning
confidence: 96%
See 1 more Smart Citation
“…KSHV ORF45 inhibits type I interferon by blocking phosphorylation and nuclear accumulation of IRF-7 (14,(33)(34)(35). It can efficiently activate RSK, eIF4B, and ERK (36)(37)(38)(39)(40)(41). The interaction between KSHV ORF45 and SIAH-1 promotes ubiquitination and proteasomal degradation of the protein (42).…”
Section: Discussionmentioning
confidence: 99%